Spinal Cord Injury and Bladder Dysfunction: New Ideas about an Old Problem - Célia Duarte Cruz; Francisco Cruz (The Scientific World Journal)
Control of the lower urinary tract (LUT) requires complex neuronal circuits that involve elements located at the peripheral nervous system and at different levels of the central nervous system. Spinal cord injury (SCI) interrupts these neuronal circuits and jeopardizes the voluntary control of bladder function. In most cases, SCI results in a period of bladder areflexia, followed by the emergence of neurogenic detrusor overactivity (NDO). Only recently, researchers have started to have a clearer vision ofthe mechanisms of SCI-induced changes affecting LUT control. For example, changes in the urothelium have recently been described and proposed to play a role in NDO. As such, a better understanding of NDO has generated new opportunities to investigate novel therapeutic approaches for NDO.In the present paper, we aim to update recent data concerning SCI-induced LUT dysfunction and therapeutic approaches commonly used to deal with NDO. We make a brief description of LUT control and changes occurring after SCI, and refer to new therapeutic options, including vanniloids and botulinum toxin. Finally, we discuss mechanisms of spinal cord repair, an interesting and very active area of investigation that has obtained some promising results in the recovery of LUT control.